Processing and characterizations of rotary linear needleless electrospun polyvinyl alcohol(PVA)/Chitosan(CS)/Graphene(Gr) nanofibrous membranes - Ting-Ting Li; Mengxue Yan; Yanqin Zhong; Hai-Tao Ren; Ching-Wen Lou; Shih-Yu Huang; Jia-Horng Lin (Journal of Materials Research and Technology, 2019)
The traditional electrospinning needles are easily blocked and the processing is not suitable for mass production. In order to address the problems, this study uses a rotary linear electrode for electrospinning for the production of polyvinyl alcohol (PVA)/chitosan(CS)/graphene(Gr) nanofibrous membranes. The membranes are observed for micro-structure and tested for thermal stability, surface resistivity, and hydrophilicity, thereby examining the influence of the content of chitosan. The test results show that the presence of chitosan improves the hydrophilcity as well as affects the morphology of PVA/CS/Gr nanofibrous membranes where the nanofiber diameter is smaller. Moreover, FTIR results suggest that chitosan and PVA interact to generate hydrogen bonds that stabilize the thermal properties of nanofibrous membranes. In particular, the maximum thermal decomposition temperature of PVA/CS/Gr nanofibrous membranes composed of PVA/CS ratio being 9:1 is 297.7 ℃. Finally, using chitosan also increases the electrical conductivity and decreases the surface resistivity. This fabricated technique provides the possibility of mass-production of PVA/CS/Gr nanofibrous membranes in the future. Keywords: Rotary linear electrospinning, Nanofibrous membrane, Chitosan, Graphene, Thermal stability, Conductivity